Controversy Over the Candidacy of Gibran Rakabuming Raka as Vice Presidential Candidate in Legal Review - Antonius Sepsia Melando; Moch Rio Basyari (Jurnal Hukum dan HAM Wara Sains, 2024)
Research This aim for give understanding about How the legality of Gibran as vice president chosen, and how legality of Anwar Usman as panel of judges of the Constitutional Court in judge decision Number 90/PUU-XXI/2023. Method used in study This that is method normative juridical with use approach qualitative. Result of study This that is that MK Judge Anwar Usman was proven violate code ethics judiciary with violate principle impartiality as well as violate the principle of nemo judex in causa sua. Study this also explains the legality of Gibran as vice president elected, Gibran indeed considered the vice presidential candidate who violated ethics law in his candidacy. However, although Lots debate, Gibran remains became Vice President validly elected.